Impact of Climate Change on Economy of Nepal with Special Edges on Tourism Industry: Threats to Development and Stability - Saidur Rahman; Sukanta Sarkar (International Journal of Climate Conditions, 2024)
Nepal is rich in biodiversity with Himalayan ecosystems and natural resources. Nepal's natural resources are a valuable and cultural asset for local communities, as well as supporting many of the country's industries. Safety is an important part of nature tourism and can attract or repel tourists. Climatic factors include temperature, precipitation, clouds, air, wind, and humidity. A key component of the industry's expansion is making traveler access safe and simple. Climate change will change the environment in which tourists come and change demand. Nepal’s climate is diverse and complex, affected by uneven terrain and regional climate. Nepal is considered a vulnerable country to climate change due to its economic, physical, geographical and political diversity. In Nepal, the effects of climate change have resulted in unparalleled losses and devastation. Nepal is extremely susceptible to the consequences of both natural disasters and climate change. The impact of climate change on the world's susceptibility to earthquakes and floods is significant. Weather-related disasters, floods, earthquakes, floods and severe weather conditions cause loss of life, property and livelihood, and seriously damage all security and economic conditions in the country. Climate change will directly affect tourist arrivals and reduce business income. The relationship between foreign visitor arrivals and Nepal's GDP is positive. Therefore, before a real disaster occurs, the government must implement the necessary policies to mitigate the impact and save the economy.
Keywords: Climate change; Environmental impact; Global Warming; Nepal economy; sustainable tourism